EFFECTS OF MARIJUANA ON SODIUM AND POTASSIUM (NA+ & P+) IONS HOMEOSTASIS AMONG SMOKERS IN BENIN CITY- A METROPOLITAN CITY IN NIGERIA - OSADOLOR.H.B; EMOKPAE; A.MATHIAS (International Journal of Pharma and Bio Sciences, 2010)
Serum sodium and potassium ions levels of marijuana smokers were estimated using atomic emission flame spectrophotometry on hundred (100) subjects comprising sixty (60) marijuana smokers and forty (40) non -marijuana smokers. The non smokers were apparently healthy subjects that served as controls. The mean of serum Na+ and K+ levels of marijuana smokers were 119±26mmol/l and 2.3±0.7mmol/l respectively, while the controls had 140±6mmol/l and 3.8±0.5mmol/l respectively. The results obtained showed that there is statistical difference in serum (electrolyte) sodium and potassium levels of marijuana smokers compared with non-smokers control (P<0.05).This work reveals that there is decrease in serum Na+ and K+ levels in marijuana smoking .Hyponatreamia and hypokelamia are the probable causes of these various mobility and mortality associated with this habit. It is suggested that marijuana smoking should be avoided.